FOOD INSECURITY STATUS AMONG FEMALE HEADED HOUSEHOLDS IN NIGERIA - Waheed Mobolaji ASHAGIDIGBI; Olaniyi Adewale AFOLABI; Iyabo Bosede ADEOYE (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Previous studies have established high food insecurity status among women compared to their male counterpart. Thus, this study examined the factors responsible for the high level of food insecurity status among female headed households in Nigeria. Secondary data obtained from Harmonized Nigeria Living Standard Survey (HNLSS) conducted by the National Bureau of Statistics (NBS) was used for the study. Information from four thousand nine hundred and seventy nine (4,979) households was used for this study. The analytical techniques adopted include descriptive statistics, Foster Greer and Thorbeck and Tobit Regression Model. The results showed that most of the female headed households’ ages lie within the range 18-60 years and 66.62% of the household were predominantly in the rural sectors. Findings revealed that 59.1% of female headed households are food insecure. Identified determinants of food insecurity among female headed households include: age of household head, household size, gender and marital status. Food availability remained below the required levels for larger parts of the rural populace identified. It is recommended that group specific safety net measure directed towards the food insecure female headed households who are predominantly widows should be an option in tackling food insecurity.